2016
DOI: 10.1080/14712598.2016.1214266
|View full text |Cite
|
Sign up to set email alerts
|

Cellular immunotherapy for malignant gliomas

Abstract: Introduction Cancer immunotherapy has made much progress in recent years. Clinical trials evaluating a variety of immunotherapeutic approaches are underway in patients with malignant gliomas. Thanks to recent advancements in cell engineering technologies, infusion of ex vivo prepared immune cells have emerged as promising strategies of cancer immunotherapy. Areas covered Herein, the authors review recent and current studies using cellular immunotherapies for malignant gliomas. Specifically, they cover the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 120 publications
0
27
0
1
Order By: Relevance
“…9,10). We have demonstrated that tumor-specific type 1 CD8 + T cells, which predominantly secrete IFN-γ, but not type 2 CD8 + T cells, can efficiently traffic into brain tumor sites and mediate effective tumor cell killing (11) via the type 1 chemokine CXCL10 (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…9,10). We have demonstrated that tumor-specific type 1 CD8 + T cells, which predominantly secrete IFN-γ, but not type 2 CD8 + T cells, can efficiently traffic into brain tumor sites and mediate effective tumor cell killing (11) via the type 1 chemokine CXCL10 (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…When comparing the TIL effectiveness in different cancers including malignant gliomas, the use of TILs against melanoma is of highest efficiency; however, 50% of melanomas do not reproduce antitumor TILs . This might be a result of the level of accessibility to eligible TILs which is largely dependent upon the tumor characteristics including its size, location, and immunogenicity . An important factor in making a lymphocyte suitable for ACT is its telomere length which is correlated with the persistence of T cells and clinical response after ACT .…”
Section: Tumor‐infiltrating Lymphocytesmentioning
confidence: 99%
“…Moreover, ACT with TILs is time-consuming and expensive. 48 When comparing the TIL effectiveness in different cancers including malignant gliomas, 49 the use of TILs against melanoma is of highest efficiency; however, 50% of melanomas do not reproduce antitumor TILs. 38,[50][51][52] This might be a result of the level of accessibility to eligible TILs which is largely dependent upon the tumor characteristics including its size, location, and immunogenicity.…”
Section: Tumor-infiltrating Lymphocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…CARs can auto signal leading to persistent activation causing potentially lethal cytokine release syndrome in addition to immunologic exhaustion. While the vast majority of ACT technology have focused on T cells, there is interest in expanding this to a variety of MHC unrestricted immune cells including NK cells, cytokine induced killer (CIK) cells and lymphokine activated killer cells (LAK) [95,96,97,98]. …”
Section: Augmenting Interaction Between Effector Cells and Tumor Cmentioning
confidence: 99%